Identification of SARS-CoV-2 Variants and Their Clinical Significance in Hefei, China - Cheng, Xiao-wen; Li, Jie; Zhang, Lu; Hu, Wen-jun; Zong, Lu; Xu, Xiang; Qiao, Jin-ping; Zheng, Mei-juan; Jiang, Xi-wen; Liang, Zhi-kun; Zhou, Yi-fan; Zhang, Ning; et al. (Frontiers in Medicine, 2022)
The ongoing coronavirus disease 2019 (COVID-19) pandemic represents one of the most exigent threats of our lifetime to global public health and economy. As part of the pandemic, from January 10 to March 10, 2020, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) began to spread in Hefei (Anhui Province, China) with a total of 174 confirmed cases of COVID-19. During this period, we were able to gather critical information on the transmission and evolution of pathogens through genomic surveillance. Particularly, the objective of our study was to track putative variants of SARS-CoV-2 circulating in Hefei for the first time and contribute to the global effort toward elucidating the molecular epidemic profile of the virus. Patients who showed symptoms of COVID-19 were routinely tested for SARS-CoV-2 infections via RT-PCR at the First Affiliated Hospital of Anhui Medical University. Whole-genome sequencing was performed on 97 clinical samples collected from 29 confirmed COVID-19 patients. As a result,, we identified a local novel single-nucleotide polymorphism site (10380) harboring a G→T mutation (Gly→Val) in Hefei. Further phylogenetic network analysis with all the sequences of SARS-CoV-2 deposited in GenBank collected in East and Southeast Asia revealed a local subtype of S-type SARS-CoV-2 (a1) harboring a C→T synonymous mutation (Leu) at position 18060 of ORF1b, likely representing a local SARS-CoV-2 mutation site that is obviously concentrated in Hefei and the Yangtze River Delta region. Moreover, clinical investigation on the inflammatory cytokine profile of the patients suggested that mutations at positions 18060 (the shared variable site of subtype a1) and 28253(harboring a C→T synonymous mutation, Phe) were associated with milder immune responses in the patients.